PENGARUH KEPUTUSAN INVESTASI, LIKUIDITAS, KEBIJAKAN DIVIDEN, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Ika Septiani; Anita Wahyu Indrasti (Universitas Budi Luhur, 2021)
This study aims to test the influence of Investment Decisions, Liquidity, Dividend Policy, and Profitability on Company Value on State-Owned Enterprises Companies listed on the Indonesia Stock Exchange for the period 2015-2019. The data used is secondary data obtained from www.idx.co.id. The population of this research is all state-owned enterprises companies listed on the Indonesia Stock Exchange for the period 2015-2019. The method of determining samples in this study used purposive sampling method with a sample as many as 20 companies. This study used multiple linear regression analysis techniques. The results showed that investment decisions and liquidity has no effect on the company’s value, dividend policy and profitability have a positive and significant effect on the company's value. The amount of influence of investment decision, liquidity, dividend policy, and profitability on the company's value is 56.3%.